An Analytical Study of the Jordanian Foreign Trade (Exports and Imports) Reality for the Period (2000-2011) (Global Journal of Management and Business Research, 2013)
International trade is considered as one of the basic criteria which reflects development reached by the country, and it is one of the tools that achieve and maintain balance since that the structure of foreign trade is specified according to country’s economic infrastructure. For example, all exported goods of countries which depend on agricultural sector will be raw materials and agricultural products. As a result, deve-lopment process in these countries will be followed by changes in foreign trade structure. In this study, we are going to examine improvements that happened in Jordanian international trade components, and their geographical distribution, which shows the economic relationship between Jordan and the external universe.
Keywords: foreign trade (ft); export (e); import (i); commodity mix (cm); balance of payments (bop); free on board (fob); cost insurance and freight (cif)